Mitochondrial cytochrome b sequence data are not an improvement for species identification in Scleractinian corals - Wares, John (PeerJ PrePrints, 2014)
There are well-known difficulties in using the cytochrome oxidase I (COI) mitochondrial gene region for population genetics and DNA barcoding in corals. A recent study of species divergence in the endemic Caribbean genus Agaricia reinforced such knowledge. However, the growing availability of whole mitochondrial genomes may help indicate more promising gene regions for species delineation. I assembled the whole mitochondrial genome for Agaricia fragilis from Illumina single-end 250bp reads and compared this sequence to that of the congener A. humilis. Although these data suggest that the cytochrome b (CYB) gene region is more promising, comparison of all available Scleractinian CYB sequence data indicates that multilocus approaches are still probably necessary for phylogenetic and population genetic analysis of recently-diverged coral taxa.
Keywords: coral; barcoding; mitochondrial DNA